Odnos Bosne i Dubrovnika u prvoj deceniji XV vijeka - Muhamed Husejnović (Historijska Misao, 2017)
The Bosnian Kingdom in the first decade of the fifteenth century was disunited. Most of disunity was brought by Bosnian nobles. They held separately their territories and in those territories they behaved like real masters. They were issuing commands and entering into contractual arrangements and by such actions undermined the political, social and economic power of Bosnia. The Bosnian king Stjepan Ostoja was dissatisfied with the policy of the nobles. He tried to establish a strong central government. In order to improve its reputation Ostoja tried to return from Dubrovnik the Slansko coast. He began with charges against their inhabitants. He also asked for some concessions. When the Republic had not agreed to the concessions he decided to return by force the territory which he sold in 1399. At the beginning of the conflict some nobles were also with the king However, effective Dubrovnik diplomacy succeeded in preventing the nobles of further attacks. The war left serious consequences on King Ostoja and on Dubrovnik merchants. After his great defeat the king had to leave the throne and Dubrovnik merchants during the war, under intense pressure, were forced to leave the Bosnian kingdom, especially the richest marketplaces.